Book reviews. Issue 1 (1st April 2017) - Leonard, Neil; Steane, Jamie
Sustainable Graphic Design: Principles and Practices, Peter Claver Fine (2016) London: Bloomsbury, 256 pp., ISBN: 9780857850638, p/bk, £28.99Becoming a Successful Graphic Designer, Neil Leonard (2016) London: Bloomsbury, 192 pp., ISBN: 9781472591197, p/bk, £26.99